COVID-19 IMPACT ASSESSMENT ON HOTEL BUSINESS IN PATTAYA CHONBURI - Jeerapattranant , Varadorn; Setarnawat, Sakchai (Journal of MCU Nakhondhat, 2023)
The objectives of this study were (1) to study the entrepreneurial orientation and marketing mix (7Ps) that influence competitive advantage and (2) to study the characteristics of entrepreneurs. Marketing Mix (7Ps) and competitive advantage influencing impact assessment of Hotel and accommodation businesses amid the COVID-19 pandemic crisis using descriptive research, the samples were entrepreneurs, business owners or executives or decision-makers who operate businesses in the category of hotels and accommodation for small and medium sized businesses operating in the Pattaya city. Sample are 360 people used a questionnaire developed from a literature review as a tool used to collect data. Statistical analysis by mean, frequency, percentage, standard deviation and variance. Data were analyzed using Structural Equation Modeling (SEM) techniques using a statistical significance level of 0.05. The study found that Entrepreneurs' opinions about entrepreneurial orientation were at a high level. The level of opinion about the overall marketing mix was at the highest level and the level of opinions about the overall competitive advantage was at the highest level. The results of the hypothesis testing revealed that the developed model was consistent with the empirical data and all variables could explain the variance of the business impact assessment of 63.9 percent marketing mix and competitive advantage Influencing the assessment of the impact of hotel and accommodation businesses under the crisis of the spread of the COVID-19 virus in Pattaya City, Chonburi Province. statistically significant.